DAMPAK IMPLEMENTASI KEBIJAKAN SERTIFIKASI TERHADAP KINERJA GURU SERTIFIKASI DI SMAN 4 PEKANBARU - Rahayu, Dina; Syahza, Almasdi; Suarman, Suarman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: In 2005, Indonesian government issued teacher certification policy, this is for increasing the performance of educators. Certified teachers are expected to increase their performance and show their professionalism as educators in the both school and society. Therefore, this is needed to find out whether the certification policy has already influenced on the increasing of teachers’ performance. This research is aimed to Analyze the Impact of Implementing Certification Policy on the Certified Teachers’ Performance at SMAN 4 Pekanbaru. Besides, this research is also to develop and enhance knowledge and how the performance should be expected in certification policy. It is also to see the reality in the work place. The data used in this research is secondary data that is the assessment of teachers’ performance assessed by school. In order to find out the impact of implementing certification policy on the teachers’ performance, this research used quantitative comparative method. Data is analyzed by t-test analysis. The result of research showed that certification policy implementation has already effected on the increasing of teachers’ performance by comparing the average score of certified teachers’ performance (51,48) with uncertified teachers’ performance (48,58). It means that the average score of certified teachers is higher than uncertified teacher as well as the result of statistical test showed the difference of performance score which is score thitung (4,4770) > ttabel(1,6871). KeyWord: The Impact ofCertification, Teacher Performance